Bridge Builders: African Experiences With Information and Communication Technology - Council, National Research; Affairs, Policy and Global; Affairs, Office of International; Africa, Panel on Planning for Scientific and Technological Information (STI) Systems in Sub-Saharan (National Academies Press, 2000)
This volume tells 16 remarkable stories-first person accounts of how information and communication technologies have been successfully introduced into institutions for the benefit of scientists and engineers in sub-Saharan Africa. These case studies focus on the lessons learned in designing and implementing projects dealing with scientific and technological information and examine the impact.